Role of Slow-Release Phosphate Nanofertilizers in Forage Nutrition and Phosphorus Lability - Reis, Heitor Pontes Gestal [UNESP]; Giroto, Amanda Soares; Guimarães, Gelton Geraldo Fernandes; Putti, Fernando Ferrari [UNESP]; Pavinato, Paulo Sérgio; Teles, Ana Paula; Ribeiro, Caue; Fernandes, Dirceu Maximino [UNESP] (American Chemical Society (ACS), 2022)
Up to 80% of the applied phosphorus via fertilizers can be lost to the environment through adsorption and precipitation reactions. Although nanoparticulated fertilizers can improve phosphate efficiency, they should be kept with no agglomeration, e.g., by dispersing urea (nanocomposite), which also provides nitrogen for plants. Thus, we evaluated the phosphorus dynamics in the soil and nutrient supply to Panicum maximum cv. BRS Zuri(Zuri grass) through three model nanocomposite fertilizers, hydroxyapatite (HAP), Bayóvar rock phosphate (BAY), or triple superphosphate (TSP), dispersed in urea-starch matrices in granular form. The experiments were done in pot experiments, analyzing the chemical composition of forage and soil after each cut. After four cuts, the treatment with the TSP nanocomposite resulted in a higher number of tillers and a higher root dry matter. However, HAP and its composites showed a similar performance to TSP in the first cut for these parameters. Plants grown with TSP have absorbed more phosphorus than those supplemented by nanocomposites (considering similar dry matter yields), which suggests that the release of nutrients from nanocomposites is better adjusted to plants' needs, promoting a better phosphorus use efficiency
Keywords: fertilizers; nanotechnology; Panicum maximum; phosphate fertilizer efficiency; Zuri grass